2021
DOI: 10.1042/cs20201017
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hypertension: lessons from spontaneously hypertensive rats (SHR)

Abstract: Although numerous clinical and experimental studies have clearly identified a sexual dimorphism in blood pressure control, the mechanism(s) underlying gender differences in blood pressure remain unclear. Over the past two decades, numerous laboratories have utilized the spontaneously hypertensive rats (SHR) as an experimental model of essential hypertension to increase our understanding of the mechanisms regulating blood pressure in males and females. Previous work by our group and others have implicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 125 publications
(256 reference statements)
1
15
0
1
Order By: Relevance
“…9,17,29,31 Estrogens are cardioprotective, reduce cardiomyocyte oxidative, ischemic, and hypertensive stress and promote vasodilation in the peripheral vasculature and coronary arteries while inhibiting the development of atherosclerosis. 32,33 However, in older women and pharmacological doses, estrogen might have adverse effects on the vessel wall. 34 Lowering estrogen levels in aging women has been linked to increased sodium sensitivity.…”
Section: Woman-specific Pathophysiology Of Hypertensionmentioning
confidence: 99%
“…9,17,29,31 Estrogens are cardioprotective, reduce cardiomyocyte oxidative, ischemic, and hypertensive stress and promote vasodilation in the peripheral vasculature and coronary arteries while inhibiting the development of atherosclerosis. 32,33 However, in older women and pharmacological doses, estrogen might have adverse effects on the vessel wall. 34 Lowering estrogen levels in aging women has been linked to increased sodium sensitivity.…”
Section: Woman-specific Pathophysiology Of Hypertensionmentioning
confidence: 99%
“…Next, we curated a list of transcripts or biological processes that were documented in the literature and mapped them to our transcriptomic data. 5,56 As shown in Figure 3 and Supplemental Table 6, these transcripts were involved in multiple physiological functions of the kidney, including sodium transport, 13,14 glucose transport, [15][16][17] water transport, 18 organic anion transport, 19,20 drug metabolism, 21 tight junctions, 14 sex hormone receptors, 22 RAAS, 57,58 adrenergic receptors, 23 and ammonia metabolism. 24,25 For example, Slc22a6 (Oat1), the basolateral sodium-dependent organic anion transporter, was primarily expressed in male PTS2, while Slc22a8 (Oat3), the basolateral sodium-independent organic anion transporter, was in female PTS2.…”
Section: Rna-seqmentioning
confidence: 99%
“…In SHR rats, sex differences have been associated, among other causes, with increased sympathetic outflow due to dysfunctional regulation of presynaptic α-adrenoceptors in males [ 93 ]. Regarding the MUN model, we have reported that females counteract better the effects of foetal stress and do not develop hypertension in adult life [ 46 ].…”
Section: Discussionmentioning
confidence: 99%